Genetic characterization of six species of diplozoids (Monogenea; Diplozoidae) - Matejusová, I; Koubkova, B; D'Amelio, S; Cunningham, C O (Parasitology, 2001)
The second internal transcribed spacer (ITS2) of the ribosomal RNA gene array of 6 species of diplozoids; Eudiplozoon nipponicum, Paradiplozoon bliccae, P. homoion, P. megan, P. pavlovskii and P. sapae, was amplified by PCR and sequenced. These sequences clearly demonstrate discrimination at the species level and confirm the validity of species determined by morphological identification. No intraspecific variation was found in the ITS2 sequences. There were no differences in the ITS2 sequences of P. homoion from populations parasitizing different host species. The length of the PCR product allowed discrimination of E. nipponicum from the Paradiplozoon species. Digestion of the amplified ITS2 fragment with enzymes AluI, HaeIII and HinfI provided useful genetic markers for species identification. The genetic relationships between diplozoids again demonstrated that E. nipponicum was the most genetically distinct species, whereas P. bliccae and P. sapae were the species most closely related. This represents the first molecular taxonomic study of these interesting parasites and demonstrates the utility of these methods for addressing questions of systematics.
Keywords: mezerníky ribozomální DNA; sekvenční homologie nukleových kyselin; polymorfismus délky restrikčních fragmentů; Polymerase Chain Reaction; polymerázová řetězová reakce; DNA, Helminth; Animals; molekulární sekvence - údaje; sekvence nukleotidů; Molecular Sequence Data; Sequence Alignment; Polymorphism, Restriction Fragment Length; Cyprinidae; Sequence Homology, Nucleic Acid; DNA helmintů; sekvenční seřazení; DNA, Ribosomal Spacer; zvířata; fylogeneze; Base Sequence; Trematoda; Phylogeny